To whom it may concern: International human rights law and global public goods - Daniel Augenstein (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2015)
Public goods and human rights are sometimes treated as intimately related, if not interchangeable, strategies to address matters of common global concern. The aim of the present contribution is to disentangle the two notions to shed some critical light on their respective potential to attend to contemporary problems of globalization. I distinguish the standard economic approach to public goods as a supposedly value-neutral technique to coordinate economic activity between states and markets from a political conception of human rights law that empowers individuals to partake in the definition of the public good. On this basis, I contend that framing global public goods and universal human rights in terms of interests and values that 'we all' hold in common tends to conceal or evade conflicts about their proper interpretation and implementation. This raises important normative questions with regard to the political and legal accountability of global ordering in both domains. The public goods approach has responded to this problem through extending the scope of political jurisdiction over public goods to encompass all those 'affected' by their costs and benefits. This finds its counterpart in attempts in the human rights debate to legally account for the global human rights impacts of public goods through extending human rights jurisdiction beyond state territory. By way of conclusion I contend that both approaches are indicative of a 'horizontal' transformation of statehood under conditions of globalization aimed at recovering the public good beyond the international order of states.
Keywords: 320; human rights; public goods; globalization; jurisdiction; extraterritorial